Semiotic Analysis Of Satire Meme Connecting Women’s Identity In Brillio Net - rr.astri indriana octavita (Scope : Journal of English Language Teaching, 2019)
This research shows that the origins of the confusion surroundings the theoretical status of cyber technology memes today could be found in culture. Those memes later developed in memetics the science of memes. Memes are a common way for individuals to communicate online. Internet users often use memes to reply to each other on social networking sites or other online forums. This research argues that memes are successfully used for communication purposes because certain memes (specifically image macros) are essentially speech acts and are also understood as being speech acts by internet users. When creating a meme, choices are made concerning the specific semiotic resources to be used and the internet community then interprets these resources to facilitate communication between the meme creator and the internet community. Memes can be recreated for different purposes and therefore it is possible to group memes under already existing speech acts and speculate about the ways in which these might correspond to speech acts in the future.